Effect of EPA on Neonatal Pig Sertoli Cells “In Vitro”: A Possible Treatment to Help Maintain Fertility in Pre-Pubertal Boys Undergoing Treatment With Gonado-Toxic Therapies - Arato, Iva; Ceccarelli, Veronica; Mancuso, Francesca; Bellucci, Catia; Lilli, Cinzia; Ferolla, Piero; Perruccio, Katia; D’Arpino, Alessandro; Aglietti, Maria Chiara; Calafiore, Riccardo; Cameron, Don F.; Calvitti, Mario; et al. (Frontiers in Endocrinology, 2021)
The incidence of cancer in pre-pubertal boys has significantly increased and, it has been recognised that the gonado-toxic effect of the cancer treatments may lead to infertility. Here, we have evaluated the effects on porcine neonatal Sertoli cells (SCs) of three commonly used chemotherapy drugs; cisplatin, 4-Hydroperoxycyclophosphamide and doxorubicin. All three drugs induced a statistical reduction of of 5-hydroxymethylcytosine in comparison with the control group, performed by Immunofluorescence Analysis. The gene and protein expression levels of GDNF, were significantly down-regulated after treatment to all three chemotherapy drugs comparison with the control group. Specifically, differences in the mRNA levels of GDNF were: 0,8200±0,0440, 0,6400±0,0140, 0,4400±0,0130 fold change at 0.33, 1.66, and 3.33μM cisplatin concentrations, respectively (**p < 0.01 at 0.33 and 1.66 μM vs SCs and ***p < 0.001 at 3.33μM vs SCs); 0,6000±0,0340, 0,4200±0,0130 fold change at 50 and 100 μM of 4-Hydroperoxycyclophosphamide concentrations, respectively (**p < 0.01 at both these concentrations vs SCs); 0,7000±0,0340, 0,6200±0,0240, 0,4000±0,0230 fold change at 0.l, 0.2 and 1 µM doxorubicin concentrations, respectively (**p < 0.01 at 0.1 and 0.2 μM vs SCs and ***p < 0.001 at 1 μM vs SCs). Differences in the protein expression levels of GDNF were: 0,7400±0,0340, 0,2000±0,0240, 0,0400±0,0230 A.U. at 0.33, 1.66, and 3.33μM cisplatin concentrations, respectively (**p < 0.01 at both these concentrations vs SCs); 0,7300±0,0340, 0,4000±0,0130 A.U. at 50 and 100 μM of 4- Hydroperoxycyclophosphamide concentrations, respectively (**p < 0.01 at both these concentrations vs SCs); 0,6200±0,0340, 0,4000±0,0240, 0,3800±0,0230 A.U. at 0.l, 0.2 and 1 µM doxorubicin concentrations, respectively (**p < 0.01 at 0.1 and 0.2 μM vs SCs and ***p < 0.001 at 1 μM vs SCs). Furthermore, we have demonstrated the protective effect of eicosapentaenoic acid on SCs only at the highest concentration of cisplatin, resulting in an increase in both gene and protein expression levels of GDNF (1,3400±0,0280 fold change; **p < 0.01 vs SCs); and of AMH and inhibin B that were significantly recovered with values comparable to the control group. Results from this study, offers the opportunity to develop future therapeutic strategies for male fertility management, especially in pre-pubertal subjects.